Characterization of Feijoa sellowiana leaves based on volatile and phenolic compound compositions and antimicrobial properties - Cebi, Nur; Sagdic, Osman (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
In the present research study, response surface methodology (RSM) was performed on the basis of total phenolic content of aqueous feijoa leaf extracts. The total phenolic content of experimental runs changed between 941.6 and 4347.5 mg GAE/L. HPLC-DAD analysis was performed to monitor the phenolic profile of feijoa leaf extract. Major phenolic compounds were determined as gallic acid, catechin, syringic acid, ellagic acid, chrysin, caffeic acid, p-coumaric acid, ferulic acid, and quercetin. Profile of volatile compounds was determined by using GC-MS technique and limonene, linalool and caryophyllene were detected as major volatile compounds. In addition, extracts from feijoa leaves showed antimicrobial activity against Gram-positive and Gram-negative bacteria and one yeast species. Taken together, all findings enhance our understanding of further use feijoa leaves as potential source for valuable bioactive compounds in various industrial products such as dietary supplements, food products (syrups, jams), and cosmetic products.
Keywords: feijoa leaves; RSM (response surface methodology); volatile profile; phenolics; antimicrobial; ULTRASOUND-ASSISTED EXTRACTION; ANTIOXIDANT ACTIVITIES; OPTIMIZATION; FRUIT; LEAF; L.; Food Science & Technology